Role of Meox1 in promoting lung tumor vascularization and impairing CD8+ T cell mediated immunity - Yang, Dacheng; Li, Qian; Chen, Zisheng; Zhang, Wei Kevin (Frontiers in Oncology, 2025)
IntroductionEndothelial cells play a critical role in tumor-associated vasculature formation and immune modulation, and dysregulation of transcription factors (TFs) such as Meox1 has been associated with various cancers, including non-small cell lung cancer (NSCLC). Meox1 has been implicated in promoting both tumor-promoting and immune-suppressing functions.MethodsIn this study, to systematically map TF dynamics across cancer and immune cells, we performed scRNA-seq on tumor tissues and used the SCENIC framework for regulon analysis, revealing cell-type-specific gene regulatory networks. We investigated the functional role of Meox1 in NSCLC by employing a siRNA-based knockdown approach to selectively reduce its expression.ResultsOur preliminary findings reveal that siRNA-mediated Meox1 knockdown significantly impairs the capacity of tube formation at the cellular level. Furthermore, we observed a marked reduction in tumor cell proliferation and an increase in CD8 expression, a marker of T-cell activity in an animal model system, indicating that Meox1 may also play a regulatory role in immune-mediated tumor suppression.DiscussionOur findings not only deepen our understanding of the molecular mechanisms underlying lung cancer progression but also open new avenues for the development of targeted therapies aimed at restoring tumor-associated endothelial cell function and enhancing immune responses against cancer.